2023
DOI: 10.59717/j.xinn-life.2023.100030
|View full text |Cite
|
Sign up to set email alerts
|

Absolute quantification of the microbiota spatial distribution in the murine large intestine

Wen-Yu Jin,
Jia-Xin Guo,
Meng Zhang
et al.

Abstract: <p>The species diversity, abundance, and location of intestinal bacteria bear major consequences on host intestinal functions, affecting the balance between health and disease. Recent studies addressed the relative abundance of bacteria in feces and on the gut mucosal surface. However, few of these publications reported the absolute number of bacteria in different compartments of the gut, especially those associated with the intestinal epithelial surface, compared to the luminal content reflected by fece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Indepth genetic analyses, particularly pertaining to the LPS transport and biosynthesis machinery under the duress of antibiotic stress, are imperative. Pahil, K. S. et al 3 complements Zampaloni, C. et al 1 findings by unveiling a novel antibiotic mechanism targeting the LPS transport pathway in Acinetobacter. This research, showcasing a unique approach by trapping LPS within its transporter, underscores the significance of inhibiting LPS transport for bacterial membrane integrity.…”
mentioning
confidence: 74%
“…Indepth genetic analyses, particularly pertaining to the LPS transport and biosynthesis machinery under the duress of antibiotic stress, are imperative. Pahil, K. S. et al 3 complements Zampaloni, C. et al 1 findings by unveiling a novel antibiotic mechanism targeting the LPS transport pathway in Acinetobacter. This research, showcasing a unique approach by trapping LPS within its transporter, underscores the significance of inhibiting LPS transport for bacterial membrane integrity.…”
mentioning
confidence: 74%
“…Wen-Yu Jin 1,2 Jing Peng 3 Jinping Dai 3 Rongkang Tang 1 Jia-Xin Guo Email: wangjielin369@126.com Wen-Yu Jin and Jing Peng contributed equally to this study.…”
Section: Conflict Of Interest Statementmentioning
confidence: 99%
“…The intestinal microbiota is host to an exceedingly large number of bacteria, estimated to be about 10 11 CFU/g in the adult colon [ 1 ]. With the development of metagenomics, metabolomics, and other omics technologies [ 2 ], the composition and function of gut microbes have been further analyzed and recognized [ 3 ]. Existing studies have shown that metabolites of the gut microbiota may be associated with the development of a variety of diseases [ 4 ].…”
Section: Figurementioning
confidence: 99%